1991
DOI: 10.1002/lary.1991.101.4.416
|View full text |Cite
|
Sign up to set email alerts
|

Patency Rate of Endoscopic Middle Meatus Antrostomy

Abstract: A series of 145 patients with chronic sinusitis were treated with functional endoscopic sinus surgery. Patency of the middle meatus was evaluated by actuarial life‐table methods. After 24 months' followup, the overall patency rate of endoscopic middle meatotomy was 94.08%. Questionnaire data indicated that 91.8% of these patients were improved or asymptomatic. This preliminary study indicates that the patency rate of middle meatal antrostomy appears to be greater than that of inferior meatal antrostomy when co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 13 publications
4
15
0
Order By: Relevance
“…Numerous reports have addressed the efficacy and safety of revision ESS, but frequently these reports did not address the surgical causes of failure 1–22 . Kuhl and Schultz‐Coulon 24 found that success of revision ESS was similar to primary ESS, with an 8.8% complication rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports have addressed the efficacy and safety of revision ESS, but frequently these reports did not address the surgical causes of failure 1–22 . Kuhl and Schultz‐Coulon 24 found that success of revision ESS was similar to primary ESS, with an 8.8% complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…ESS is the most common procedure performed for the treatment of chronic sinusitis. Since its inception in 1985, reports of its success have ranged from 76% to 97.5% 1–17 . Conversely, 2.5% to 24% of patients continue to be symptomatic.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have been published on the efficacy of FESS in the treatment of chronic sinus disease after medical failure. The overall success rate for endoscopic surgery ranges from 80% to 97% depending on the criteria used to establish success 1‐6,10‐15,19‐23 . Most of these studies are based on subjective symptomatic relief and short‐term follow‐up.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature shows that endoscopic follow‐up is primarily based on middle meatal antrostomy (MMA) patency rate as the only objective criteria for success 2‐4,10,13 . Overall patency rates of endoscopically created MMAs range from 85% to 93% 2‐4,10,13 . To our knowledge, there are no studies that have evaluated postoperative endoscopic findings as they relate to patient symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Continued comparisons in the human model, however, have shown differences in long‐term patency rates. Davis et al 6 established long‐term patency of the middle meatal antrostomy at 94.6% compared with approximately 70% historical patency for the inferior meatal antrostomy. Moreover, analysis of ciliary flow patterns in rabbits by Kennedy and Shaalan 7 revealed that the nasal antral window did not cause “redirection of the mucociliary clearance pattern.” That is, the cilia in the sinus continue to clear mucus toward the natural ostium, despite surgical alteration.…”
Section: Introductionmentioning
confidence: 99%